Penerapan Prinsip Total Quality Management dalam Meningkatkan Kepuasan Peserta Didik di Madrasah Aliyah Negeri 2 Kudus - Erna Susanti; Subaidi Subaidi; Muhammad Khoiruddin (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to analyse the implementation of Total Quality Management (TQM) principles in enhancing student satisfaction at Madrasah Aliyah Negeri 2 Kudus. The main issues examined include: 1) how TQM is implemented at MAN 2 Kudus, 2) the factors that encourage and inhibit the implementation of TQM, and 3) the impact on student learning outcomes and the overall quality of education. This research employs a qualitative method with data collection techniques including observation, interviews, and documentation. The data obtained were analysed through the process of reduction, presentation, and conclusion drawing. The findings reveal that: 1) the implementation of TQM at MAN 2 Kudus involves all school elements--from leadership and teachers to students--with a focus on continuous improvement in educational services, learning processes, and resource management; 2) the main driving factors for successful TQM implementation are leadership commitment, active participation of all school members, and the emerging quality culture. However, challenges still exist, such as limited understanding of TQM principles among some teachers and staff, as well as inadequate supporting facilities. 3) The positive impact of TQM implementation is reflected in the increased student satisfaction with educational services, a more conducive learning atmosphere, and improvements in learning outcomes and graduate quality. The study recommends ongoing training on TQM for the entire academic personnel and strengthening of the internal quality assurance system. These findings are expected to serve as a reference for other educational institutions in optimizing TQM implementation to improve quality and student satisfaction.